Pentingnya Menjadi Pemilih Cerdas Menuju Pemilu Berkualitas dan Berintegritas Pada Pemilu 2024 - Eva Susanti; Aldi Setiawan; Nabila Aisyah; Tia Oktafiani Putri; Vikka Rosdiana Nova; Opi Ismarita (Universitas 45 Surabaya, 2023)
Elections are indicators or benchmarks in a democratic country. The means of sovereignty are realized in the form of citizens' voting rights, a general election that is based on direct, general, free, secret, honest and fair purposes to elect leaders who will continue the previous leadership relay with the aim of continuing, managing government administration and serving all levels of society. Voters have a big role in Indonesia's leadership in the upcoming 2024 election. If the wrong leader is chosen, it can result in the destruction of the nation and state. The method used in this socialization activity is as follows: (1) the lecture method is used to explain material related to